Perlindungan Hukum Bagi Konsumen Air Minum Dalam Perjanjian Jual-Beli Air Bersih: (Studi Di Perumda Amerta Dayan Gunung KLU) - Baiq Liza Wati; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine and analyze the legal relationship between PERUMDA Amerta Dayan Gunung and consumers and to identify and analyze forms of legal protection for consumers in drinking water services by PERUMDA Amerta Dayan Gunung. The type of legal research used in conducting this research is the type of empirical normative legal research. From the results of the research that has been carried out, the results related to the legal relationship between PDAM North Lombok Regency and consumers the, namely the first agreement for the installation of the North Lombok Regency PDAM, the second a water meter rental agreement, and the third a water sale and. In terms of the form of legal protection for consumers, there are two forms of legal protection, the first is preventive legal protection, which is the protection provided to prevent violations. Second, repressive protection is protection that is given if there has been a violation.